Comparison of Coagulant Dose (Poly Aluminum Chloride) Use in The Water Treatments Process of Kalimalang River - Deniela Flora Mariyne Wongso Diharjo; Jannie Jannie; Wahyu Sekti Retno Permatasari; Temmy Wikaningrum (Fakultas Teknik, 2022)
River has a vital role to fulfill the water needs of the community. In the water bodies, the small suspended particles, also known as colloids, with the small weight and stability in the water bodies they have, they cannot be settled or eliminated naturally. There are some concerns regarding colloid removal in Kalimalang river, such as increase in water turbidity resulting the decrease in the river water quality as a water source and disruption of the ecosystem in the river. The experiment used poly-aluminum chloride (PAC) as the coagulant and jar test method which contains coagulation-flocculation process. This aims to determine optimal dosage of PAC to reduce the turbidity and pH value of water sample that relate to the regulation of water quality standard for sanitary hygiene, which is regulated by law No 32 Year 2017. The optimum dose for this experiment is 2 mg/L PAC 0.5 percent as the sample achieved the lowest average of turbidity that is 0.02 NTU with the average of pH is 7, indicating that the sample meets the quality standards of Environmental Health Quality Standards for sanitary hygiene purposes.